2014
DOI: 10.1155/2014/648137
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Association of theXRCC3Gene Polymorphism with Ovarian Cancer Risk

Abstract: This meta-analysis aims to examine whether the XRCC3 polymorphisms are associated with ovarian cancer risk. Eligible case-control studies were identified through search in PubMed. Pooled odds ratios (ORs) were appropriately derived from fixed effects models. We therefore performed a meta-analysis of 5,302 ovarian cancer cases and 8,075 controls from 4 published articles and 8 case-control studies for 3 SNPs of XRCC3. No statistically significant associations between XRCC3 rs861539 polymorphisms and ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 40 publications
0
32
0
1
Order By: Relevance
“…X-ray repair complementing defective repair in Chinese hamster cells 3 ( XRCC3 ) belongs to a family of genes responsible for repairing DNA double strand breaks caused by normal metabolic processes or exposure to ionizing radiation [20]. XRCC3 proteins are recruited to a DSB during the S and G2/M phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray repair complementing defective repair in Chinese hamster cells 3 ( XRCC3 ) belongs to a family of genes responsible for repairing DNA double strand breaks caused by normal metabolic processes or exposure to ionizing radiation [20]. XRCC3 proteins are recruited to a DSB during the S and G2/M phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, rs1799794 has been observed associated with increased risk of overall cancer [50], breast cancer [23], bladder cancer [51, 52]. Nevertheless, decreased risk of ovarian cancer has also been observed in some of the studies [20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The double-strand break DNA repair pathway, including XRCC2 gene, is implicated in maintaining genomic stability and therefore could affect cancer risk. Common genetic polymorphisms in DNA repair genes might affect protein function and thus the capacity of repair DNA damage, which in turn could lead to genetic instability [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Eitan et al (10) identified miR-200a, miR-34a, and miR-449b as the most downregulated miRNAs in advanced Association between the rs11614913 variant of miRNA-196a-2 and the risk of epithelial ovarian cancer (11) reported the association of high levels of miR-196a expression and worse overall survival in ovarian cancer patients, especially in advanced stage tumors. Single nucleotide polymorphisms (SNPs) have also been examined as potential EOC risk indictors (12)(13)(14). However, the mechanism and genetic factors involved in the progression of this cancer remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%